2017
DOI: 10.5603/kp.a2016.0185
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-3 is associated with coronary plaque burden and obstructive sleep apnoea syndrome severity

Abstract: A b s t r a c tBackground: Obstructive sleep apnoea syndrome (OSAS) is reported to be associated with hypertension, coronary artery disease, atrial fibrillation, and heart failure. Galectin-3 plays an important role in the regulation of inflammation, development of cardiac fibrosis, and remodelling. A significant relationship between galectin-3 and the total number of coronary plaques and the macrocalcified plaque structures of patients with type 2 diabetes mellitus has been reported. Aim:The aim of this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
15
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
1
15
0
Order By: Relevance
“…Our results suggest a significant burden of non-calcified plaques in OSA. This is in line with some previous studies (Murphy et al, 2017;Sharma et al, 2012); however, other investigations showed no difference in non-calcified plaques in OSA (Kent et al, 2013;Pusuroglu et al, 2017). We found only a trend for higher CAC values in OSA.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results suggest a significant burden of non-calcified plaques in OSA. This is in line with some previous studies (Murphy et al, 2017;Sharma et al, 2012); however, other investigations showed no difference in non-calcified plaques in OSA (Kent et al, 2013;Pusuroglu et al, 2017). We found only a trend for higher CAC values in OSA.…”
Section: Discussionsupporting
confidence: 93%
“…Segment stenosis score was significantly higher in obstructive sleep apnea (p < 0.01) F I G U R E 3 Comparison of coronary artery calcium scores. Coronary artery calcium score tended to be higher in obstructive sleep apnea (p = 0.07) criteria for OSA, ranging from AHI score of 5/hr (Matthews et al, 2011;Medeiros et al, 2017;Nakanishi-Minami et al, 2012;Sorajja et al, 2008;Weinreich et al, 2013) to 10/hr (Sharma et al, 2012), in addition to the combination of objective measures and symptoms (Pusuroglu et al, 2017). We hypothesised that even mild OSA may be associated with CAD (Hu et al, 1999); therefore, we chose AHI score of 5/hr as a diagnostic threshold without taking into account symptoms or comorbidities.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations